Job Search Behavior among the Employed and Non-Employed - R. Jason Faberman; Andreas I. Mueller; Aysegül Sahin; Giorgio Topa (Institute of Labor Economics (IZA), 2017)
Using a unique new survey, we study the relationship between search effort and outcomes for employed and non-employed workers. We find that the employed fare better than the non-employed in job search: they receive more offers per application and are offered higher pay even after controlling for observable characteristics. We use an on-the-job search model with endogenous search effort and find that unobserved heterogeneity explains less than a third of the residual wage offer differential. The model calibrated using various moments from our survey provides a good fit to the data and implies a reasonable flow value of unemployment.
Keywords: E24; J29; J60; 330; job search; unemployment; on-the-job search; search effort; wage dispersion